Analisis Implementasi Fatwa DSN-MUI Nomor 54 Tahun 2006 Terhadap Produk iB Hasanah Card Bank BNI Syariah - Arzani, Teny Khotimah; -, Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
This study describes the implementation of the iB Hasanah Card operational financing at BNISyariah Bank which is adjusted to the DSN-MUI Fatwa Number 54 of 2006 (Syariah Card), to findout the suitability between the iB Hasanah Card operations against the sharia card mechanismbased on the fatwa. The method used in this research process is a qualitative descriptive analysismethod. Retrieval of data in the form of primary data, and secondary data, primary data obtained byconducting interviews with the BNI Syariah Bank. Literature study was obtained from books, journals,official websites and documents relating to the iB Hasanah Card. The data analysis technique wascarried out with three steps, namely data reduction, data presentation, and drawing conclusions fromthe results of the data analysis as evidenced by the validity of the data through source triangulationtechniques. The results of this study indicate that the BNI Syariah Bank in general in carrying out theoperational iB Hasanah Card as a whole is in accordance with the fatwa DSN-MUI No.54 / DSNMUI/ X / 2006. However, there are a number of points from the iB Hasanah Card program featuresand provisions regarding restrictions that should need special attention and be reviewed, becausethe contents contained in the fatwa are usually general or comprehensive, not specific or detailed.Like, smart spending and danlus features on iB Hasanah Card that are not listed in the fatwa. Otherprovisions include differences in fee provisions and the application of ta’widh fees, the calculation ofwhich is based on the time period of delay and the type of card not based on the actual loss incurredby the bank during billing.